Molecular cloning and functional analysis of a plastidial ω3 desaturase from Emiliania huxleyi - Sun, Kaiwen; Meesapyodsuk, Dauenpen; Qiu, Xiao (Frontiers in Microbiology, 2024)
Emiliania huxleyi is a marine microalga playing a significant ecological and biogeochemical role in oceans. It can produce several polyunsaturated fatty acids (PUFAs), such as docosahexaenoic acid (DHA,7,10,13,16,19) and octadecapentaenoic acid (OPA,6,9,12,15), providing a primary source for nutritionally important w3 PUFAs in the marine food chain. However, the biosynthesis of these PUFAs in this organism is not well understood. In this study, a full length plastidial w3 desaturase cDNA (EhN3) was cloned from this alga. Heterologous expression of EhN3 with and without the chloroplast targeting peptide (cTP) in cyanobacterium Synechococcus elongatus showed that it possessed high desaturation activity towards C18-w6 PUFAs, linoleic acid (LA, 18:2-9,12), g-linolenic acid (GLA, 18:3-6,9,12), and C20-w6 PUFAs, dihomo-g-linolenic acid (DGLA,11,14) and arachidonic acid (ARA,8,11,14) that were exogenously supplied. Desaturation efficiency could reach almost 100% in a time course. On the other hand, when expressed in Saccharomyces cerevisiae, EhN3 with and without cTP did not exhibit any activity. Lipid analysis of Synechococcus transformants expressing EhN3 showed that it utilized galactolipids as substrates. Transcriptional expression analysis revealed that the expression of the gene increased while the growth temperature decreased, which was correlated with the increased production of w3-PUFAs, particularly OPA. This is the first report of a plastidial w3 desaturase from microalgae that can effectively introduce an w3 double bond into both C18-w6 and C20-w6 PUFAs. EhN3 might also be one of the key enzymes involved in the biosynthesis of OPA in E. huxleyi through the plastidial aerobic pathway.